A comparative study on the application of the convention for the elimination of all forms of discrimination against women on the labour laws of Malaysia and Australia / Nurul Huda Padulli…[et al.] - Padulli, Nurul Huda; Mohd Shahar, Nur Shahira; Azaharee, Nur Annisa (Faculty of Law, 2007)
This research project paper is a requirement for the LW213 - Bachelor of Legal Studies (Hons) course offered in Universiti Teknologi MARA. It is done as a follow-up to the subject Legal Research and Methodology completed last semester. This research project addresses the issue of women's rights in Malaysia. It will compare and contrast the situation in Australia with that of the situation in Malaysia. This is because Australia has enacted several legislation that are specifically catered for women. This research project will study whether Malaysia would be able to draw upon Australia's laws and apply it in the Malaysian context. An important element of this research is the application of the Convention on the Elimination of All Forms of Discrimination Against Women, which is a United Nations human rights treaty. This research will also study the application of this Convention into the labour laws of Malaysia and Australia. On completing this research, we have found that Malaysia can indeed draw upon Australia's examples in addressing the issue of women's rights. However, this needs to be done at a gradual pace and in an appropriate manner to the customs and practices of Malaysians. The Legislature will have to look into whether the society in Malaysia is ready to adopt certain laws and whether it will contravene any other laws in Malaysia.